Seizure characteristics and the use of anti-epileptic drugs in children and young people with brain tumours and epileptic seizures: Analysis of regional paediatric cancer service population. (May 2018) - Pilotto, Chiara; Liu, Jo-Fen; Walker, David A.; Whitehouse, William P.
Highlights: Epileptic seizures are a neurological complications in children with brain tumour. Seizure treatments and their withdrawal are not codified. In our cohort we found a relationship between tumour site and seizure occurrence. Levetiracetam was used for its good tolerability and poor interaction with chemotherapy. Further studies are required to assess the time of AEDs withdrawal. Abstract: Purpose: Epileptic seizures complicate the management of childhood brain tumours. There are no published standards for clinical practice concerning risk factors, treatment selection or strategies to withdraw treatment with antiepileptic drugs (AED). Method: we undertook a case note review of 120 patients with newly diagnosed brain tumours, referred to a regional paediatric cancer service. Results: data was available on 117/120 (98%) children <18 years: median age at tumour presentation was 8.1 years (IQR 25°−75° : 3.6–12.7), median follow up was 33 months (IQR 25°−75°: 24–56), and 35/117 (29%) experienced seizures. A cortical tumour location was associated with the highest risk of seizures (OR: 7.1; CI 95% 2.9–17.3). At a median follow up of 24 months (IQR 25°−75° : 15–48), 22/35 (63%) with seizures, had a single seizure episode, 15/35 (43%) were seizure free (SF) on AEDs, 13/35 (37%) were SF off AEDs, and 7/35 (20%) experienced continuing epileptic seizures. Overall 34/35 (97%) were treated with AEDs after a seizure, of whom 12/35 (35%) withdrew from AED medication, and although 4/35 (12%) had seizure relapse, all were after further acute events. The median duration of AED before withdrawal was 11 months (IQR 25°−75° 5–14 months), and the median follow up after withdrawal was 15 months (IQR 25°−75° 5–34 months). Conclusions: Seizures affect about 1/3rd of children and young people presenting with and being treated for brain tumours particularly when the tumour is in the cerebral cortex. The low risk of recurrent seizures after AED treatment justifies consideration of early withdrawal of AED after seizure control.